Biochar Amendment Alleviates Cadmium In Contaminated Soil And Improves Nutrient Uptake In Rice (Oryza Sativa L.) (Applied Biological Research, 2020)
Cadmium is a toxic metallic element that, if present in high concentrations  in soil, poses severe human health risks through intake of contaminated  agricultural produces. A pot experiment was conducted in a net house to  assess nutrient uptake by rice (Oryza sativa L.) in cadmium-contaminated  soil amended with biochar. Six cadmium levels (0, 20, 40, 60, 80 and 100  mg kg-1) and three levels of biochar @ 0, 20 and 40 t ha-1, respectively, were  taken. Results indicated that nutrient content and its uptake decreased  with increasing levels of soil cadmium. Nutrient content and its uptake were significantly high in soils amended with biochar. Also, the nitrogen and phosphorus contents and their uptake weremore in grains; whereas  potassium content and its uptake were more in rice straw. Biochar may be  usedto alleviate the toxic effect of cadmium in cadmium contaminated soils.
Keywords: Biochar; cadmium; nutrient uptake; rice